2012
DOI: 10.1017/s0305000911000493
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between phonemic abilities and syllable congruency effect in young readers

Abstract: Link to this article: http://journals.cambridge.org/abstract_S0305000911000493How to cite this article: FABIENNE CHETAIL and STÉPHANIE MATHEY (2013). Interaction between phonemic abilities and syllable congruency effect in young readers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…No trace of the inhibitory syllable frequency effect was found. In the same vein, Chetail and Mathey (2013) found the syllabic compatibility effect in fifth grade (age: 11), but only for those with lower phonemic ability.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…No trace of the inhibitory syllable frequency effect was found. In the same vein, Chetail and Mathey (2013) found the syllabic compatibility effect in fifth grade (age: 11), but only for those with lower phonemic ability.…”
Section: Introductionmentioning
confidence: 80%
“…However, the advantage of a syllable–color match was greater for poor readers than good readers. A reliable syllable congruency effect was also found in a lexical decision task combined with masked priming in both sixth- (age: 11,9; Chetail & Mathey, 2012) and fifth-graders (age: 11) (Chetail and Mathey, 2013), but this effect was modulated by phonological abilities: a negative correlation was found between the syllabic effect and phonemic abilities.…”
Section: Introductionmentioning
confidence: 90%
“…Most research has focused on the statistical, orthographic and phonological properties of French to account for the syllable as an early prelexical and segmental unit in reading in typically developing children (e.g., Bastien‐Toniazzo, Magnan, & Bouchafa, ; Chetail & Mathey, , , ; Colé, Magnan, & Grainger, ; Doignon & Zagar, ; Doignon‐Camus, Bonnefond, Touzalin‐Chretien, & Dufour, ; Doignon‐Camus, Zagar, & Mathey, ) and even also in dyslexic children (e.g., Maïonchi‐Pino, Magnan, & Écalle, ). Whereas these studies have revealed contrasting frequency‐modulated findings, other studies have failed to find clear and straightforward evidence that the statistical regularities of letter co‐occurrences modulate word parsing (e.g., Chetail & Mathey, ; Doignon & Zagar, ; Doignon‐Camus et al, ; Doignon‐Camus, Seigneuric, Perrier, Sisti, & Zagar, ; Maïonchi‐Pino, Magnan, & Écalle, ).…”
Section: Introductionmentioning
confidence: 99%